(untitled) (Revista Electrónica REDINE, 2023)
The purpose of this study is to investigate the training strategies applied by swimming teachers during the teaching-learning process, to develop the elements of psychomotricity in children at the initial level inside and outside the aquatic environment in initiation schools from the Bolivarian Swimming Pool Complex, Barquisimeto-Lara. It was framed in the qualitative approach under the interpretive paradigm with the praxis of the phenomenological method. We worked with five teachers responsible for imparting the initiation in swimming and the various participants who attend the class of this specific discipline. The collection of information was carried out through participant observation techniques and in-depth interviews. An analysis, interpretation and systematization of the contents were carried out, with the application of the triangulation technique to be able to contrast and categorize the testimonies of the social actors. The final considerations of the study made it possible to show that the social actors present some drawbacks with the development of the elements of psychomotricity. In addition, they use a traditional and linear teaching method. However, they tend to familiarize children with adaptive games, activities, and exercises in the aquatic environment.